Surfactant gene polymorphisms and interstitial lung diseases - Pantelidis, Panagiotis (BioMed Central, 2002)
Pulmonary surfactant is a complex mixture of phospholipids and proteins, which is present in the alveolar lining fluid and is essential for normal lung function. Alterations in surfactant composition have been reported in several interstitial lung diseases (ILDs). Furthermore, a mutation in the surfactant protein C gene that results in complete absence of the protein has been shown to be associated with familial ILD. The role of surfactant in lung disease is therefore drawing increasing attention following the elucidation of the genetic basis underlying its surface expression and the proof of surfactant abnormalities in ILD.